Fuzzy Multi-criteria Selection of Alternatives by Quasi-best Case as the Basis for Choosing Robotic Machine-Assembling Technologies - Kyrylovych, V.A.; Dimitrov, L.V.; Melnychuk, P.P.; Belskiy, D.G.; Shadura, V.A.; Savkiv, V.B.; Kryzhanivska, I.V. (Bulletin of the Karaganda University. Mathematics Series, 2020)
The process of choosing the robotic machine - assembling technologies (RMAT) is implemented as the fuzzy multi - criteria selection of alternatives by the suggested previousely method of quasi - best case. The basic concept feature of the given method is the developed specific correlations which are based on the corresponding comparisons to better alternative Р◦nd to the most important criterion. All the mentioned above determines the practical and scientific value of this paper. The results of strict ranking of the elements of local criteria discrete set (LCDS) are input dР◦ta. It is performed by the method of expert survey and at the same time demonstrates RMAT phenomenon. The idea of selections the process of ordering constituents of initially unordered LCDS elements which finally form ordered set. The selection is performed within the set of these elements. The obtained ordering of RMAT phenomenon as a result of selection is recommended to be analyzed in the process of choosing. The base of solving the task of RMAT selection is its formalized description and on its base the generalized content formalisms of quasi - best case method are determined. The performance of the presented the theoretical issues is demonstrated step - by - step with the real example of the automated RMAT selection.